Analysis of the Impact of Smartphone Use on Adolescent Social Interactions During COVID-19 - Mellania Indrasvari; Risma Delima Harahap; Dahrul Aman Harahap (Postgraduate, University of Mataram, 2021)
This study is titled Analysis of Smartphone Use against Adolescent Social Interactions During COVID-19. This research is motivated by the increasingly popular use of smartphones among generation Z that can influence social interactions especially the outbreak of the Covid-19 virus that urged students to study at home or online by using smartphones and keeping activities out of the house in order to avoid the Covid-19 virus and break the chain of the virus that causes constrained social interaction activities outside the home, especially the students of grade XII science 1 and XII science 2 at Senior High School 2 Rantau Selatan (State Senior High School 2, South Rantau) (State Senior High School 2, South Rantau) using qualitative-descriptive research that considered suitable for the problem of the impact of smartphone use on adolescent social interactions during the Covid-19 period where the main data sources in this study are students. The tools used to collect data are questionnaires, interviews, observations and documentation. Sampling technique used is purposive sampling. The sample data from this study were students of grade XII science 1 & XII science 2 with a total of 64 people. The results of the interview research and supported by the questionnaire showed that the use of smartphones in students in grade XII science 1 and XII science 2 Senior High School 2 Rantau Selatan (State Senior High School 2, South Rantau) (State Senior High School 2, South Rantau) was at 51.02%, then about 33.84% intensity of social media to eliminate saturation only activities in the house alone that resulted in a lack of intensity or association of teenagers with people around the next student doing activities gathered with friends categorized as small enough only 5.08% is also caused by the government's rules to stay at home and 10.06% of students feel the effects of smartphones. The conclusion of this study shows that there are positive and negative impacts of smartphones on adolescent social interactions during Covid-19